Penerapan Model Pembelajaran Snowbal Throwing Dalam Rangka Meningkatkan Prestasi Belajar Al-Qur’an Hadits pada Siswa MTs Sunan Giri Kelas VIII A Tahun Ajaran 2014-2015 - Ratnawati, Ratnawati (TADARUS, 2016)
Motivation to learn Al-Quran Hadith is a force, impetus, or tool builder willingness and strong desire for self-learners for active learning, creative, effective, innovative and enjoyable in order to obtain optimal learning results. Throwing Snowball learning model is a model of learning in which there are elements of the game and is expected to evoke the spirit of student learning. This study aims to determine whether throwing snowball learning model can improve students' motivation class VIII A MTs Sunan Giri The results showed an increase in class VIII student motivation A MTs Sunan Giri which resulted in the increase of learning outcomes, ranging from pratindakan activities, cycle I and cycle II. In preaction research students who have mastery learning as much as 52.63% after the action learning model Snowball Throwing mastery learning students in the first cycle increased to 92.11% and the second cycle continued mastery learning students rose to 97.37%. The conclusion that can be drawn is that the learning model throwing Snowball can increase students' motivation class VIII A MTs Sunan Giri, so that the learning outcomes have increased as well. Another finding is that the child becomes happy, the spirit and confidence in the learning process.